piRNAs, master regulators of gene expression - Simonelig, Martine (Nature Publishing Group, 2014)
Piwi-interacting RNAs (piRNAs) have a major function in the repression of transposable elements in the germline; in addition, they have been proposed to regulate gene expression. A recent study in Cell Research reveals a general role for piRNAs in the massive mRNA decay during mouse spermiogenesis, reinforcing this emerging function of piRNAs.